Influence of renal function and daptomycin dose on clinical effectiveness and adverse events in Japanese pediatric patients: A multicenter retrospective observational study. - Chihiro Shiraishi; Hideo Kato; Jun Hirai; Naoya Nishiyama; Takayuki Inagaki; Nobuyuki Ashizawa; Masashi Nakamatsu; Kazuko Yamamoto; Yasuhiro Miyagawa; Hiroyuki Honda; Satoshi Kakiuchi; Ayumi Fujita; et al. (PLoS ONE)
Background Data on the clinical effectiveness and adverse events of daptomycin in pediatric patients, considering dosage and renal function, are limited. Aim In this study, we aimed to investigate the clinical effectiveness of daptomycin, incidence of related adverse events, and associations between clinical outcomes and risk factors, including dosage and renal function, in pediatric patients. Methods Medical records of pediatric patients treated with daptomycin between September 2011 and December 2022, were retrospectively reviewed. Clinical effectiveness was categorized as cure, improvement, failure, or non-evaluable. The clinical success rate was defined as the sum of cured and improved cases. We classified doses based on the approved ranges: underdose (>1 mg/kg less than the approved dose), adequate dose (approved dose ±1 mg/kg), and overdose (>1 mg/kg more than the approved dose). Obesity was defined as a body mass index ≥ 30 kg/m2, with adjusted body weight used for dosing in these patients. Findings We enrolled 54 patients, achieving a clinical success rate of 91%. Four (7%) patients died, particularly those with microbiological failure (P = 0.004) and underdosing (P < 0.001). The underdose group comprised a higher proportion of younger patients (P = 0.020). Additionally, seven (13%) patients experienced daptomycin-related adverse events, including creatine phosphokinase elevation, eosinophilic pneumonia, rhabdomyolysis, liver failure, and drug fever, occurring regardless of renal function. Five patients received an approved dose, while two received an overdose. Conclusion Adequate daptomycin dosing improved clinical effectiveness and the mortality rate. However, continuous monitoring of adverse events remains critical for patients receiving the approved dose, including those with a normal renal function.